(3cJGH YHO Gddg Hf GdMQ, cJGH OjGJs - (3GHf GdoMQ, YHO Gddg Hf GdMQ, YHO Gddg Hf SYjO Hf MfGf Hf GdMQ GdcfGfj, J (B240(3g` (B854(3es
(3ChdgG (B:s
(3ChdgG(B: (3aEf aj GdCUhd GdeYJHQI GdeYJeOI GdeTghQI GdJj cGf EdjgG GdeQLY aj CYUGQ CUMGH (B..s
(3BNQgG (B:s
(3CNQgG(B: (3aj QLd GaJV LGQjI HCUHYg aNQb eKGfJgG, adG Jedc HhdgG, aLYd KdK GdOjI eFI hSJI hSJjf OjfGkQG hKdGKI OjfGQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf L (B2: 244s
(3EjVGM Gdecfhf L (B2: 296s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3abg GdePGgH GdCNQis